Tacrolimus pharmacogenomics in abdominal solid organ transplantation - Falconer, Stuart John (The University of Edinburgh, 2018)
Background: Abdominal solid organ transplantation has evolved from an experimental procedure to a well-established therapy within a few decades. This success is largely due to the introduction of calcineurin inhibitor immunosuppression. Tacrolimus is the most widely used calcineurin inhibitor but has a narrow therapeutic range which requires close drug monitoring to prevent both toxicity and inadequate immunosuppression. Previous studies in renal transplantation have shown that genetic polymorphisms, CYP3A5, CYP3A4*22 and ABCB1 can influence the bioavailability and pharmacokinetics of tacrolimus. These polymorphisms are closely linked to ethnicity and have never been studied in a Scottish population before. Additionally, increasing evidence suggests that high variability of tacrolimus is linked to increased graft loss in kidney transplant patients. Methods: 5889 subjects were genotyped for the genetic polymorphisms CYP3A5 A>G allele transition, CYP3A4*22 C>T and ABCB1 C>T transition. This included 4899 healthy individuals from Generation Scotland bio-resource and 990 patients who underwent renal, liver, or simultaneous pancreas kidney transplants or were organ donors. Tacrolimus dose, trough level and renal function were measured at 11 time points from date of transplant up to and including 12 months post-transplant. Clinical data including episodes of acute rejection, graft and patient survival were compared between the different genotypes. Separate analyses were undertaken for kidney, SPK transplants, as well as liver transplants, the latter looking at recipient and liver donor genotype. A separate cohort of 103 renal transplant patients converted from twice-daily to once-daily tacrolimus had their tacrolimus variability calculated and compared with graft survival. Results: The distribution of the 3 different genotypes of CYP3A5, CYP3A4*22 and ABCB1 were comparable with other Caucasian populations studied previously. In renal transplant recipient expression of the A allele (GA/AA) led to significantly increased dose requirements of tacrolimus and initially lower tacrolimus trough levels. The different genotypes of ABCB1 had no effect. Expression of a CYP3A4*22 T allele trended towards a lower tacrolimus dose requirement but this was not significant. There was no difference in renal function, graft survival or patient survival with any of the polymorphisms. SPK patients had comparable results. In the liver transplant patients, the donor genotype had a greater influence than the recipient one. The donors with CYP3A5 A allele expression had significantly higher tacrolimus dose requirements and lower initial tacrolimus levels. This was apparent to a lesser extent with the recipient expression of CYP3A5 and did not reach statistical significance at all time points. There was no significant difference in tacrolimus dose requirements or level with either donor or recipient expression of ABCB1 or CYP3A4*22. There was a significantly higher incidence of acute rejection in donor CYP3A5 A allele expressers of liver transplant patients in univariate and multivariate analysis. There was no significant different in acute rejection with ABCB1 or CYP3A4*22 genotype. No differences in graft or patient survival with either donor or recipient genotype of any of the 3 polymorphisms were noted. Conversion from twice-daily to once-daily tacrolimus in the first 12 months post-transplant reduced tacrolimus variability. Patients with high tacrolimus variability pre and post conversion had significantly greater graft loss than patients with low tacrolimus variability. Conclusion: CYP3A5 expression results in increased tacrolimus requirements to achieve adequate immunosuppression in renal transplant and SPK patients. Donor rather than recipient CYP3A5 expression is relevant for liver transplantation and dose requirements. There may be an association with donor CYP3A5 expression in liver transplant patients and acute rejection which needs further evaluation. ABCB1 and CYP3A4*22 do not appear to have a significant impact in any of the organ transplants. High tacrolimus variability is associated increased graft loss in renal transplant patients.
Keywords: transplant rejection; tacrolimus; CYP3A5; slow release formulation; ABCB1 genes; CYP3A4*22 genes; clinical outcome; kidney transplant